Intangible assets investment and firms’ performance: evidence from small and medium-sized enterprises in Korea - Seo, Hyeon Sik; Kim, YoungJun (Journal of Business Economics and Management, 2020)
While many studies have examined the relationship between investment in intangibles assets and performance in large corporations, current research is lacking in regard to intangible investments in small and medium enterprises (SMEs). This study looks at SMEs in which intangible investments would usually be minor because they tend to consider intangible investment as an inefficient cost and concentrate on investments in tangible assets. This paper aims to contribute to the current literature and suggests that investment in the intangible assets of (human capital, advertising, R&D) is essential for SMEs pursuing superior firm performance. Actual data collected from 173 SMEs in Korea were analyzed employing hierarchical regression methodology. Results indicate that all three intangible resources have a positive effect on a firm’s profitability and value. Interestingly, this research finds that investment in advertising has the most influential impact on a firm’s profitability and value. This study has implications for SMEs in achieving their profitability and value. The results in this study highlight that intangible investment is not a waste of money for SMEs, and that business managers could strategically utilize these three key contributors (human capital, advertising, R&D) and adopt investment in intangible assets to accomplish their managerial goals.